2005
DOI: 10.1677/joe.1.06333
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of inbred mouse strain (C57BL/6, DBA/2, 129T2) on insulin secretory function in response to a high fat diet

Abstract: The increasing production of genetically-modified mouse models has necessitated studies to determine the inherent physiological characteristics of commonly used mouse strains. In this study we examined insulin secretory function in response to an intravenous bolus of glucose or glucose plus arginine in anesthetized C57BL/6, DBA/2 and 129T2 mice fed either a control or high fat diet for 6 weeks. The results show that 129T2 mice had higher fasting plasma glucose levels and lower fasting plasma insulin levels com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
102
2
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(121 citation statements)
references
References 34 publications
(19 reference statements)
13
102
2
4
Order By: Relevance
“…Although they showed the largest increase in body weight and also gained substantial amounts of fat mass, they became only marginally glucose intolerant on the HFD, as reported previously [1]. They exhibited similar differences in lipid accumulation, mitochondrial metabolism, inflammation and oxidative stress to other strains.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Although they showed the largest increase in body weight and also gained substantial amounts of fat mass, they became only marginally glucose intolerant on the HFD, as reported previously [1]. They exhibited similar differences in lipid accumulation, mitochondrial metabolism, inflammation and oxidative stress to other strains.…”
Section: Discussionsupporting
confidence: 81%
“…They exhibited similar differences in lipid accumulation, mitochondrial metabolism, inflammation and oxidative stress to other strains. However, they did exhibit a large increase in fasting insulin, suggesting that compensatory hyperinsulinaemia reduces HFD-induced glucose intolerance in this strain [1,4].…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…We found that in contrast to C57BL/6 mice, which have a genetic disruption in Nnt, and the 129T2 mice, which show low levels of expression, the diabetes-susceptible DBA/2 mice show a fivefold overexpression of this gene, which encodes the mitochondrial proton pump known as nicotinamide nucleotide transhydrogenase. Insulin secretion was elevated in DBA/2 mice relative to that in C57BL/6 and 129T2 mice [18][19][20] Interestingly, we found that other strains of mice (BALB/c, FVB/N) that have previously been shown to be susceptible to diabetes when subjected to genetically induced obesity and insulin resistance also displayed increased NNT activity. We suggest that reduced NNT levels in the C57BL/6 and 129T2 strains result in lowered insulin secretion and mild glucose intolerance [21], and that protection against the development of diabetes in response to genetically induced obesity and insulin resistance may paradoxically be due to a reduced ability of the beta cell to secrete insulin.…”
Section: Ermentioning
confidence: 57%